Update on Hittite latti: an Anatolian-Greek isolexeme? - Puhvel, Jaan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Critically reconsidering, updating, and improving the treatment of the noun latti- in earlier work, weighing a semantic and/or etymological affinity as ‘share, lot, part’ with the Greek verbs νέμω and λαγχάνω.